2013
DOI: 10.1021/pr300973q
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Clostridial Glucosylating Toxins and Their Function on Colonocytes Analyzed by Proteomics Techniques

Abstract: Clostridium dif f icile is the major cause of intestinal infections in hospitals. The major virulence factors are toxin A (TcdA) and toxin B (TcdB), which belong to the group of clostridial glucosylating toxins (CGT) that inactivate small GTPases. After a 24 h incubation period with TcdA or a glucosyltransferase-deficient mutant TcdA (gdTcdA), quantitative changes in the proteome of colonic cells (Caco-2) were analyzed using high-resolution LC−MS/MS and the SILAC technique. The changes in abundance of more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 70 publications
(161 reference statements)
2
61
0
Order By: Relevance
“…Statistical tests are indicated with horizontal lines as described in the legend to S10). In another high-throughput analysis of the host cell response to TcdA, Zeiser et al analyzed the changes in the proteome of Caco2 cells 24 h after TcdA exposure (47). By mapping transcripts to proteins, we found that the proteomics data were poorly correlated with transcriptional changes in HCT8 cells and our in vivo data (r 2 Ͻ 0.01 for all comparisons).…”
Section: Discussionmentioning
confidence: 71%
“…Statistical tests are indicated with horizontal lines as described in the legend to S10). In another high-throughput analysis of the host cell response to TcdA, Zeiser et al analyzed the changes in the proteome of Caco2 cells 24 h after TcdA exposure (47). By mapping transcripts to proteins, we found that the proteomics data were poorly correlated with transcriptional changes in HCT8 cells and our in vivo data (r 2 Ͻ 0.01 for all comparisons).…”
Section: Discussionmentioning
confidence: 71%
“…Analysis-These analyses were performed as described previously (40). Reversed-phase chromatography of peptide samples was conducted with a nano-flow ultra-high-pressure liquid chromatography system (RSLC, Thermo Fisher Scientific).…”
Section: Lc-ms/ms and Automated Ms Datamentioning
confidence: 99%
“…'HeLa Whole Cell Lysate' was used as positive control lysate, while detection of the abundantly expressed loading control vinculin was applied [20,21] to calculate relative ALDH2 expression in blood samples. Detailed information regarding the generation of protein lysates from frozen whole blood samples, relative ALDH2 protein quantification and validation of precise detection of ALDH2 by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) as described earlier [22] , can be found in the online supplementary material.…”
Section: Western Blot Analysis Of Relative Aldh2 Protein Quantificatimentioning
confidence: 99%